High-profile crime and perceived public safety: Evidence from Cologne's new year's eve in 2015 - Martin Lange; Alexander Schmidt (ZEW - Leibniz-Zentrum für Europäische Wirtschaftsforschung, 2023)
This study analyses the impact of a high-profile crime event on perceived public safety. At the 2015 New Year's Eve celebrations in Cologne (NYE), Germany, refugees allegedly committed over a thousand crimes, ranging from theft to sexual assault. The widespread media coverage of these incidents made a shift in the public's perceived safety plausible. We empirically analyze this proposition using a difference-in-differences strategy. Using the European Social Survey, we estimate the differential response of German respondents to those of other European countries in terms of perceived safety after NYE. We find that Germans feel less safe after the NYE incidents. Women and individuals leaning toward the political right are affected the most. An analysis of search queries suggests that the loss of perceived safety may also translate into changed behavior, indicated by a higher demand for defense goods.
Keywords: J15; K42; Z13; 330; Crime; Perceived Safety; Immigration; Refugees